Effect of Social Media Marketing Activities (SMMa) and Fear of Missing Out Behavior on Purchase Intention of Hammersonic Music Concert Tickets - Cahyo Hapsoro; Novel Idris Abbas (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the impact of Social Media Marketing activities (customization, entertainment, trendiness, interaction) and Fear of Missing Out (FoMO) on the purchase intention of Hammersonic concert tickets.Methodology: Employing a quantitative method, data were collected from 250 active social media users of Hammersonic via online questionnaires. Structural Equation Modeling (SEM) with SmartPLS was used to test the relationships.Results: Results reveal a significant positive effect of all SMMa dimensions and FoMO on purchase intention, emphasizing the role of personalized and engaging digital marketing.Applications/Originality/Value: This research fills a gap by integrating multiple SMMa elements and psychological factors in the non-K-Pop concert context in Indonesia, contributing to both academic theory and practical marketing strategies in the entertainment industry.